E-cadherin and β-catenin: Dual roles in carcinogenesis: E-kadherin in β-katenin: dvojna vloga v karcinogenezi - Eskelinen, Sinikka (Acta Medico-Biotechnica, 2021)
Strict signalling control mechanisms have evolved to regulate epithelial– mesechymal transitions and regeneration of epithelial tissues, and failure of these processes may lead to carcinogenesis. These signalling processes range from regulation of gene expression and cell cytoskeleton to proliferation and apoptosis, and the central players include E-cadherin and β-catenin. These molecules function as structural elements at cell–cell contact sites and β-catenin is the key intermediate in the Wnt signalling pathway, which regulates gene expression of various proteins involved in morphogenesis and cell survival via the TCF/LEF pathway. The present review describes how the expression of E-cadherin and phosphatases act as negative regulators of Wnt signalling, promoting differentiation, whereas tyrosine kinases amplify the Wnt signalling pathway via phosphorylation of cadherins and catenins, resulting in increased proliferation and inhibition of apoptosis.